Physical random number generator based on MOS structure after soft breakdown. - Yasuda, S. (IEEE Journal of solid state circuits)
We present a novel physical random number generator (RNG) that uses a metal-oxide semiconductor (MOS) capacitor after soft breakdown (SBD) as a random source. It is known that the electrical properties of MOS capacitors after SBD show large fluctuation. When the resistor in an astable multivibrator is replaced with an MOS capacitor after SBD, the multivibrator converts the noise signal into a rectangular wave whose period fluctuates randomly. A 1-bit counter and a flip-flop are used to generate random numbers from the fluctuating rectangular wave. Some high-level tests indicate that the generated random numbers have excellent quality for cryptographic applications. Even though our circuit is small and can be constructed using about 20 complementary-MOS logic gates and several passive devices, high-quality random numbers such as those generated by large physical RNGs can be obtained.